Hubungan antara Jumlah Kepesertaan Tenaga Kerja, Jumlah Kecelakaan Kerja, dan Jumlah Jaminan Kecelakaan Kerja Perusahaan Kelompok Jenis Usaha III Peserta Program JKK pada PT Jamsostek Cabang Medan - Gerry Silaban (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: The membership of employees in Accident Benefit Program and occupational health and safety implementation at workplace are business-owner responsibility. Business group type III as the member of Employment Accident Benefit Program when not performing accident prevention efforts will not be expected to decrease employment accident to zero and it implicates in the escalation of employment accident claims.Method: The research periods were 4 months (April – August 2006) and located at PT Jamsostek Medan branch. Survey research with correlation setting was used as research method. The research samples involves 105 enterprises from business group type III as the member of Employment Accident Benefit Program at PT Jamsostek Medan Branch, which their employees experiencing employment accident during one year (January 1st until December 31st 2005), and being reported to PT Jamsostek Medan Branch and receives employment accident benefit. The research data that consist of number of employment accident and employment accident benefit were collected from Employment Accident Report Phase I (Jamsostek Form 3) and Employment Accident Report Phase II (Jamsostek Form 3a), and number of employee membership data of Accident Benefit Program at PT Jamsostek Medan Branch. Spearman’s product moment correlation was used to analyze data.Results: There is a significant relationship (p <0.01) between number of employees membership in Employment Accident Benefit Program and number of employment accident, regression coefficient was (r) = 0.258. There is strongly significant relationship (p < 0.01) between number of employment accident and number of employment accident benefit, correlation coefficient was (r) = 0.641.Conclusion: To reduce number of employment accident and employment accident benefit, business group type III must performs the occupational health and safety in order to generate healthy and safety workplace and to comply the occupational health And safety regulation. PT Jamsostek was expected to actively participating and continued supporting the occupational health and safety implementation by enterprises as the membership of Employment Accident Benefit Program and cooperates with Local Manpower Institution which also assigned on developing and supervising the occupational health and safety implementation.Keywords: membership of employees in the Employment Accident Benefit Program, employment accident, employment accident benefit